Development, Polymorphism and Cross-Species Transferability of Genomic SSR Markers in Duabanga Moluccana, an Indigenous Tree Species from Sarawak - Kit-Siong, Liew; Wei-Seng, Ho; Shek-Ling, Pang; Julaihi, Abdullah (Science Publication, 2016)
In this study, we used ISSR-suppression methods to develop a set of SSR markers for Duabanga moluccana. It is an indigenous fast growing tropical tree species. A total of 44 SSR regions were identified and specific primer pairs were designed. The SSR motifs contained perfect compound with 24 (54.5%) occurrences, followed by the imperfect compounds with 8 (18.2%), simple perfect with 8 (18.2%) and the simple imperfect repeats with 4 (9.1%). The newly identified SSR markers were characterized by screening 20 individuals of D. moluccana seedlings. Among 43 primer pairs tested, 25 (58.1%) SSR markers amplified the desired PCR products and 115 alleles were detected. The number of alleles per locus ranged from 2 to 8, with a mean value of 4.60. Polymorphism Information Content (PIC) values ranged from 0.225 to 0.792, with an average of 0.604. A success rate of transferability of D. moluccana SSR markers varied, ranging from 84% in Duabanga grandiflora, 36% in Neolamarckia cadamba, 24% in Canarium odontophyllum and 28% in Shorea parvifolia. These SSR markers herein could be used to generate useful baseline genetic information for effective selection of plus trees, provenance trials and establishment of forest Seed Production Areas (SPAs) of D. moluccana in the selected forest reserves for tree plantation and improvement activities. Besides, the transferability of the newly developed SSR markers across a range of species and genera suggests their potential usefulness for a variety of population genetic studies.